SUPPLY CHAIN ATTACK DETECTION THROUGH LIFECYCLE-AWARE ANOMALY SYSTEMS: INTEGRATION OF END-OF-LIFE CONTEXT FOR IDENTIFYING MAINTENANCE TRANSITION ANOMALIES - Дем'янчук, Сергій; Мартиненко, Роман; Лопухович, Володимир (SWorldJournal, 2026)
Supply chain attacks targeting software dependencies represent an escalating threat vector, with adversaries increasingly exploiting lifecycle transitions-particularly End-of-Life (EoL) and maintenance handover events-to introduce malicious code into trus